Studies on Macro Meso and Micromorphology and Clay Mineralogy of the Acid Sulphate Soils of Kerala - Subramonia Iyer M (Department of Soil Science and Agricultural Chemistry, College of Agriculture, 1989)
The acid sulphate soils of kerala cover an area of approximately 0.2 million hectares on the West coast of Kerala. A well integrated study on the genesis, morphology, mineralogy and certain physic – chemical properties of these soils was conducted. Aspects of its genesis, position in the global system of classification, macro, meso and micro morphology, mineralogy, both macro and micro as well as primary and secondary, physical and physic-chemical properties relevant to classification and management have received attention. The salient points of the study are highlighted emphasising conclusions pertinent to the expanding frontiers of our knowledge on these soils. The acid sulphate soils occurring along the West coast of Kerala based on morphological observations as well as stage by stage microscopical study are indicated to have been formed by sedimentation of finer material overlying and often impregnating wood fossils, faunal and floral relics in the recent geological past. The extent of alluviation, stage of degradation of the fossilised wood and incorporation of sediments and formation of secondary products vary from location to location as indicated in the study. In almost all the acid sulphate soils around the globe, pyrite is the major mineral component contributing to acidity. They have framboidal micro structure with size ranging from 15 – 50 u, However, in the acid sulphate soils of Kerala pyrrohtite (Fes) is the predominant sulphate mineral with a size range <2 µ along with small amounts of pyrite (Fes2) which also are < 2µ. These minerals have been formed in the recent geological past, under the anaerobic environment releasing ferrous iron from the alleviated soil materials especially laterite falls and the sulphur from the sulphates added by the ingress of sea water, fossilised wood and decaying organic matter. The pyrite (FeS2) and pyrrohtite (Fes) undergo oxidation especially when the aeration is encouraged by tidal influences, and acidity conditions. As has been demonstrated in the present study they are oxidised initially to ferric hydroxides and then to jarosites. The end product of oxidation of pyrite, however, varies from situation to situation in Kerala. Thus it may be jarosites as encountered in the surface soils of all the locations while the oxidation may be only to the stage of ferric hydroxide as observed in the fourth horizon of Mathikayal and Kattampally where the pyrite occurs overlying a bed of lime shells. The ripeness of the acid sulphate soils generally are decided by the extent of acidity generated on oxidation with H2O2and also the ‘n’ value of the soil which is related to the pH as well as the organic matter and clay content. On this basis all the acid sulphate soils of Kerala vary from half ripe to fully ripe. The ripe soils have been encountered only at Kattukambal in the kole area. Another factor, is the depth of occurrence of the jarosite mottle laden layer. In the acid sulphate soils of the present study, the jarosites have been located, within 50 cm. Below 50 cm pyrite and pyrrohtite are the dominant sulphur containing minerals. Among the oxidation products, the mineral lepidocrocite (Fe – O – OH) a variant of goethite has been found to be associated with pyrrohtite espeacially at the Karumadi location. The occurrence of lepidocrocite in acid sulphate soils has not been reported earlier. It is possible that it is the intermediate stage in the oxidation of pyrrohtite to jarosite. The lower layers of the acid sulphate soils have lime shells in some locations such as Mathikayal, other Kayal areas of Kuttanad and some of the pokkali and kaippad soils. The pyrites are found to be closely overlying the lime shells without suffering major alterations to either of them. Thus the pyrite frambodies have been transformed partly in a few of its microcrystals to the oxidised form of ferric hydroxides, but the acidity of the embedding soils has neither dissolved nor reacted with the lime shells. X – ray diffraction, thermogravimetric as well as chemical studies conducted with the clay indicate kaolinite as the dominant minerals in these soils. Minor quantities of mineral viz., smectite, chlorite and illite have been detected. Mica and quartz have been found in quantities equal to that of Kaolinite. It is possible that like laterite falls, fine quartz also is alleviated into these soils from the midland regions of Kerala. Soils which attain pH of 2.5 by oxidation with 100 per cent H2O2 have been considered to be dangerously acid sulphate soils. The soils in the present study attain pH values less than 2.5 even with 30 per cent H2O2. Though the upper layers are half to fully ripe. They are still found to be dangerously acid. The lower layers with more of reserve pyrites are much more dangerously acid. These observations on the acid sulphate soils are a pointer to the cropping patterns and water management to be pursued in these areas in the foreseeable future. Thus the rice crop in a waterlogged situation is possibly the only crop that may throw up lesser problems in soil management. The dangerous nature of the potential acidity especially in the lower layers have to be considered in ruling out all propositions of tree crop alternatives such as rubber and oil palm. From the present studies it has been found that these soils have only a sulphidic enrichment within 50 cm from the surface, instead of a sulphuric horizon. Further the sulphur content is also not significient enough to include them in the category of soils with sulphuric horizon. Soils with sulphuric horizon only are considered to attain a pH of 4 by airdrying and 2.5 by H2O2 treatment. The soils in the present study despite an enrichment, only with sulphidic materials attain a pH of 2.5 to 3.0 by mere airdrying and pH was low as 2.0 by H2O2 oxidation. Thus the lack of a sulphuric horizon but in its place a mere sulphidic enrichment makes them almost dangerously acid. Evidently this has to be attributed to the pyrrohtitic (Fes) nature And the smaller size (< 2µ) of the framboid conferring it to be placed as a class separate from typical acid sulphate soils reported from the rest of the world. Thus these soils from the present study are found to be more dangerously acid sulphate than others though they do not satisfy the requirement of either the total sulphur content or the presence of a typical sulphuric horizon. Further the pyrite framboids have a size range of only 1/25th of that of the framboids reported elsewhere from the globe. This has made them more dangerously acid. All the same, they require to be placed as soils with sulphidic materials rather than the soils with sulphuric horizon as per soil Taxonomy. (USDA, 1975). Nevertheless, the fact remains that these soils are highly acidic with considerable amounts of reserve pyrites and hance reserve acidity. These soils call for utmost care in their management. The acid sulphate soils of Kerala are thus to be continuously managed under a waterlogged milieu to enable optimum productivity with minimum problems due to acidity and related aspects. The possibility of growing perennial crops such as rubber and oil palm require partial to fully aerobic situations. These conditions are likely to result in oxidation of the pyrite laden layer noticed up to 90 cm in the present study. This can generate an enormous quantity of free sulphuric acid. The pyrite laden layer extends up to 90 cm in the present study. The acid sulphate soils of kerala are definitely different from Malaysian acid sulphate soils in that the surface layer is not completely free of pyrites. In view of the fact that the surface soil contains only jarosite and no pyrites, the Malayasian peats and acid sulphate soils have been subjected to cultivation with oil palm and rubber. However the Malaysian experience cannot be transplanted as such to Kerala inview of the very serious initial problems likely to be thrown off by the generation of acidity by the oxidation of pyrites under aerobic situations. Being half to full ripe, acid sulphate soils of Kerala are still dangerously acid to warrant the continuation of the existing management practices and cropping systems.